PERANCANGAN SISTEM KONTROL GLYCOL REGENERATION UNIT DENGAN DCS DeltaV DI ONSHORE GAS PLANT - Redaksi Tim Jurnal (Sutet, 2017)
The glycol regeneration process is an integrated part of the glycol dehydration unit (GDU) system. Each plant has a customized configuration to the needs of the process, for the case in this onshore field because the gas produced from the well is good enough with a fairly low water content, then does not use Glycol Contactor. Instead used low temperature separator and glycol generation unit. DCS DeltaV is used to operate, documentation and optimization of gas processes. By using oscillation method and closed loop system obtained PID tuning result with parameter P = 387, I = 57 and D = 53. The response of the control system is conditioned overshoot from its setpoint to accelerate the rise of the temperature plant. When the temperature of glycol regeneration is at 2620 F, the alarm will light Hi limit and Hi Hi limit at 2900 F, while at 2450F the alarm will light low limit and Low Low limit at temperature 00 F.